Correlation of tongue posture with dental arch characteristics in different skeletal patterns using cone-beam computed tomography - Dalaie, Kazem; Zeinali, Hamideh; Behnaz, Mohammad; Safi, Yaser; Tahmasbi, Soodeh; Sedighinia, Maryam (Journal of Dental School, 2024)
Objectives: This study assessed the correlation of tongue posture with dental arch characteristics in sagittal and vertical skeletal patterns using cone-beam computed tomography (CBCT). Materials and Methods: This cross-sectional study evaluated 225 CBCT scans of sagittal Class I, II, and III patients. Class I and II groups were subdivided into high-angle, normal, and low-angle vertical subgroups. Palatal length, width, and height, maxillary width (Wmax), mandibular width (Wman), tongue posture according to the Graber’s analysis, tongue length (TGL), and tongue height (TGH) were three-dimensionally measured. Statistical analyses were conducted using one-way and two-way ANOVA, and Pearson and Spearman tests (alpha=0.05). Results: All dental arch parameters were significantly greater in Class III, compared with Class I and II groups (P<0.05), except for) Wman, palatal length, and palatal height( . Palatal height was significantly greater in Class II and III, than Class I group (P<0.05). Wmax was lower in high-angle than low-angle, and palatal length was lower in high-angle than low-angle and normal groups (P<0.05). In Class I normal-angle patients, Wmax had a positive correlation with TGL. In Class I low-angle patients, Wmax had a moderate positive correlation with TGH. Conclusion: Significant differences were found in Wmax and palatal length among the vertical groups. In different skeletal patterns Wmax, Wman had a low to moderate positive correlations with D4, D5, D5ʹ, TGL and TGH. Wmax in Class I was significantly lower than that in Class III; this variable in Class II was significantly lower than that in Class III Palatal width in Class I and Class II was significantly lower than that in Class III. Palatal height in Class I was significantly lower than that in Class II and Class III